İBN ‘USFÛR ve ARAP DİLİNE KATKILARI [105-123] - Erdim, Enes (Fırat University, 2014)
Endülüs bölgesinin en önemli dilcilerinden biri olan İbn ‘Usfûr, dönemin ünlü hocalarından ders almış ve birçok öğrenci yetiştirmiştir. Velûd bir âlim olan İbn ‘Usfûr, geride sarf ve nahve ilişkin birçok eser bırakmıştır. Bu makalede onun hayat hikâyesine ve eserlerine yer verilerek dile ilişkin bazı görüşleri ortaya konmuştur. Böylelikle onun Arap diline olan katkısı tespit edilmeye çalışılmıştır

İbn ‘Usfûr who is one of the most important scientist of the Andalusian region had lessons from the most popular teachers of the time and educated lots of students. Ibn ‘Usfûr who wrote many books left a lot works such as morphology and sentax. In this article, by giving place to his life story and works we tried to uncover views of the device about the language. By this way, we tried to determine his contribution to the Arabic literature
Ibn ‘Usfûr and His Contribution to the Arabic Literature